(untitled) (Global Journals of Research in Engineering, 2023)
In many industries safety is paramount and the fast-track construction industry is no exception Globally more than 60 000 fatalities are reported each year due to inadequate and incompetent Fast-track construction Site Safety Management CSSM In Jordan construction workers fatalities and injuries increase year after year particularly in fast track fast-track construction projects Implementing fast-track construction site safety management is considered a significant problem on in every project Therefore it is critical to investigate the most convenient practices to ensure fast-track construction project safety to reduce death and injury rates Innovative CSSM is key to solving the current safety challenges in the Jordanian fast trackfast-track Jordanian fast-track construction industry